2022
DOI: 10.1073/pnas.2119439119
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into a spindle-shaped archaeal virus with a sevenfold symmetrical tail

Abstract: Archaeal viruses with a spindle-shaped virion are abundant and widespread in extremely diverse environments. However, efforts to obtain the high-resolution structure of a spindle-shaped virus have been unsuccessful. Here, we present the structure of SSV19, a spindle-shaped virus infecting the hyperthermophilic archaeon Sulfolobus sp. E11-6. Our near-atomic structure reveals an unusual sevenfold symmetrical virus tail consisting of the tailspike, nozzle, and adaptor proteins. The spindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Archaeoviruses can also incorporate ether lipids from their extremophilic host in their virions, which seem to protect against chemical stress ( Boyd et al, 2013 ). Archaeal lipids are also present in the structure of hyperthermophilic spindle-shaped viruses, but its location remains under debate ( Quemin et al, 2015 ; Han and Yuan, 2022 ).…”
Section: Viruses At the Planetary Scale: The Virospherementioning
confidence: 99%
“…Archaeoviruses can also incorporate ether lipids from their extremophilic host in their virions, which seem to protect against chemical stress ( Boyd et al, 2013 ). Archaeal lipids are also present in the structure of hyperthermophilic spindle-shaped viruses, but its location remains under debate ( Quemin et al, 2015 ; Han and Yuan, 2022 ).…”
Section: Viruses At the Planetary Scale: The Virospherementioning
confidence: 99%
“…The 13 formerly defined core genes [ 14 , 29 , 30 ] were kept in our analysis as part of the soft-core, and we incorporated four additional genes (A92, VP3, C102, and A100). Core genes VP1, VP3, VP4, and C166 play a structural role [ 28 , 36 , 37 , 38 ], the integrase D355 serves virus integration into the genome [ 22 ], and proteins B251 an ATPase with similarity to the bacterial DnaA [ 39 ] and A154 have been implicated in replication and packaging of the genome. Indeed, B251 and A154 are also encoded by the satellite virus pSSVx, which replicates during infection of an SSV2 helper [ 40 ].…”
Section: Genomic Analysismentioning
confidence: 99%
“…Three of these genomes (SSV NL101B.C01.09, NL101B.C01.18, and NL101B.C01.22) harbor two VP4 homologs that seem to be the result of the full protein split into its N- and C-terminal domains. For the remaining three (SSV6, SSV19, and ASSV1), it was recently reported that the short VP4 homolog serves as an adaptor protein for the tail, while another protein (belonging to OG0000087) has the same genomic location as VP4 and serves as the tail-spike [ 38 ]. A truncated VP4 and the OG0000087 tail-spike are associated with viruses that show a pleomorphic morphology [ 30 ].…”
Section: Genomic Analysismentioning
confidence: 99%
See 2 more Smart Citations